2022
DOI: 10.1073/pnas.2115567119
|View full text |Cite
|
Sign up to set email alerts
|

Postmitotic G1 phase survivin drives mitogen-independent cell division of B lymphocytes

Abstract: Significance The prevailing dogma is that renewed mitogenic signaling is essential to traverse G1 phase of the cell cycle after each division. B lymphocytes undergo multiple mitotic divisions, termed clonal expansion, to expand antigen-specific cells that mediate effective immunity. Here we demonstrate that B cells that have undergone one cell division continue to proliferate even in absence of further mitogenic signals. This mitogen-independent proliferation is accompanied by an altered G1 phase mar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Patients predicted to benefit most from this approach are those demonstrating signs of CLL proliferation in lymphoid tissues, e.g., lymphadenopathy and/or elevated blood frequency of survivin-positive leukemic cells [21] and/or CLL cells with an elevated CD5/CXCR4 ratio [73,84,85]. Both of the latter are indicators of recent cycling [73,84,86]. As recently reviewed [87], among adjunct approaches currently in clinical use to enhance venetoclax efficacy in first-line treatment of CLL, the most effective are second-generation covalent BTK inhibitors, acalabrutinib, and zanabrutinib, which in combination with venetoclax, yield patient 4-year survival rates of 88% and 94%, respectively [87].…”
Section: Discussionmentioning
confidence: 99%
“…Patients predicted to benefit most from this approach are those demonstrating signs of CLL proliferation in lymphoid tissues, e.g., lymphadenopathy and/or elevated blood frequency of survivin-positive leukemic cells [21] and/or CLL cells with an elevated CD5/CXCR4 ratio [73,84,85]. Both of the latter are indicators of recent cycling [73,84,86]. As recently reviewed [87], among adjunct approaches currently in clinical use to enhance venetoclax efficacy in first-line treatment of CLL, the most effective are second-generation covalent BTK inhibitors, acalabrutinib, and zanabrutinib, which in combination with venetoclax, yield patient 4-year survival rates of 88% and 94%, respectively [87].…”
Section: Discussionmentioning
confidence: 99%
“…Activated B cells enter the growth phase and increase in cell size, and during the growth phase, they are protected from cell death ( Figure 2 ) ( 60 , 66 ). It has been shown that mature B cells stimulated for 24 hour activate the proliferative program, and these activated B cells are programmed to divide multiple times without further stimulation, suggesting that induction of key regulators within the first few hours may control division number ( 67 ). In line with this, Heinzel et al.…”
Section: The Nfκb Signaling System In B Cell Proliferation and Survivalmentioning
confidence: 99%
“…Toll-like receptors (TLRs) found on phagocytic cells serve as a bridge between these different networks. Through their interactions with antigen-presenting cells, these receptors start off the adaptive immune response [3]. Cytokines function as cell-to-cell communication molecules [4].…”
Section: Introductionmentioning
confidence: 99%